Association between fetoplacental Doppler results, placental pathology, and angiogenic factors among pregnant women with anxiety - Heejeong Lee; Sang Hee Lee; Min Ji Ko; Sa Jin Kim; Jae Eun Shin (Elsevier, 2020)
Objective: This study aimed to evaluate whether state and trait anxiety among pregnant women were associated with fetoplacental Doppler findings, abnormal placental pathology, and placental angiogenic factors. Materials and methods: A total of 102 pregnant women at 32-35 gestational weeks were recruited and examined prospectively. State and trait anxiety were measured using the State-Trait Anxiety Inventory. Using Doppler ultrasound, pulsatility index (PI) of the umbilical artery (UA), middle cerebral artery (MCA), and uterine artery (UtA) and cerebroplacental ratio (CPR) were determined. Doppler parameters were converted into multiples of the median (MoM). Abnormal placental pathology was classified into 2 groups: vascular underperfusion (VU) and histological chorioamnionitis (HCA). Immunohistochemical analysis was performed to examine placental cells staining positive for placental growth factor (PLGF) and hypoxia-inducible factor-1-α (HIF-1α), which are markers for angiogenesis and hypoxic status, respectively. Results: Women with high state anxiety scores had low MCA-PI MoM and CPR MoM, while those with high trait anxiety scores had low MCA-PI MoM. VU was associated with a higher incidence of high trait anxiety scores, and HCA was associated with a higher incidence of high state and trait anxiety scores. Regression analysis showed a relationship between maternal state anxiety on MCA-PI MoM and HCA after controlling for covariates. Maternal trait anxiety exhibited relationships with VU and HCA after adjustment. Conclusion: Our results demonstrated that maternal anxiety is associated with altered fetal cerebral blood flow and abnormal placental pathology but is not associated with uteroplacental insufficiency and placental angiogenic factors.